2020
DOI: 10.1055/a-1216-1363
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of balloon endoscope-assisted endoscopic retrograde cholangiopancreatography for the elderly

Abstract: Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) for patients with surgically altered anatomy is challenging. Recently, balloon endoscopy has been shown to facilitate ERCP for this population with a high technical success rate, but adverse events (AEs) are not uncommon. Compared to non-elderly patients, elderly patients may be at higher risk of AEs due to underlying comorbidities. The current study aimed to evaluate the feasibility of balloon endoscope-assisted ERCP (BE-ERCP) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
10
0
2
Order By: Relevance
“…Adverse events occur in 5–18% of patients treated with this procedure [ 15 , 20 , 22 , 44 ], and the incidence rate was 5% in the present study. In contrast to conventional ERCP, perforation is one of the most common adverse events for this procedure [ 45 ] and occurs mainly during scope insertion or stone extraction.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Adverse events occur in 5–18% of patients treated with this procedure [ 15 , 20 , 22 , 44 ], and the incidence rate was 5% in the present study. In contrast to conventional ERCP, perforation is one of the most common adverse events for this procedure [ 45 ] and occurs mainly during scope insertion or stone extraction.…”
Section: Discussionmentioning
confidence: 47%
“…In addition, patients enrolled in this study were relatively elderly, showing a median age of 79 years old. A previous study also reported that both technical success rates and the rates of adverse events were similar between elderly (≥75 years old) and non-elderly groups (<75 years old), suggesting that BE-ERCP is a feasible procedure for elderly individuals with a surgically altered anatomy [ 44 ]. Repeated BE-ERCP may carry a risk for elderly patients, so middle-term stent placement may be an option for the treatment of cases of complicated CBD stones, although caution against life-threatening cholangitis should be practiced [ 4 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial literature search resulted in 4105 studies, with 76 of them [ 11 , 13 , 15 , 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ,…”
Section: Resultsunclassified
“…These techniques have showed different success rates over the years, depending mostly on the surgical alterations. Overall, sDBE-ERCP had a success rate between 70.7 and 96% [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], while SBE-ERCP appeared to be as effective as sDBE, with a success rate among 73 and 92.3% [ 36 , 37 , 38 , 39 ]. Among studies about SBE-ERCP, Lenze et al [ 40 ] in a prospective single-center study, showed a lower success rate (57.7%), but they also found in univariate analysis that malignant biliary obstruction had a significantly higher risk of SBE-ERCP failure (OR = 11.33, p = 0.001).…”
Section: Resultsmentioning
confidence: 99%